Benign Metastasizing Leiomyoma in the Lung Presenting in a Phyllodes-Like Pattern Mimicking a Biphasic Tumor: A Case Report. (April 2022) - Fadel, Saleh; Villeneuve, Patrick J.; Gupta, Ashish; Strickland, Sarah; Gomes, Marcio
Primary biphasic tumors of the lung are rare. Lung lesions with a biphasic pattern are far more commonly primary or metastatic soft tissue tumors with entrapped native respiratory epithelium, giving the false impression of a biphasic tumor. We report a case of bilateral benign metastasizing leiomyomas in a 69-year-old female where the tumor cells diffusely entrapped native respiratory glands in a phyllodes-like pattern. The radiographic characteristics and histologic appearance were not immediately diagnostic and covered a wide differential. Reaching the final diagnosis required the use of immunohistochemical studies as well as correlation with the patient's history and radiographic findings. To the best of our knowledge, this is the first report of pulmonary benign metastasizing leiomyoma presenting in a phyllodes-like pattern. This case illustrates the importance of considering entrapment of native lung epithelium in the differential diagnosis of biphasic-appearing lung tumors.